2019
DOI: 10.3389/fnagi.2019.00270
|View full text |Cite
|
Sign up to set email alerts
|

Free Water in White Matter Differentiates MCI and AD From Control Subjects

Abstract: Recent evidence shows that neuroinflammation plays a role in many neurological diseases including mild cognitive impairment (MCI) and Alzheimer's disease (AD), and that free water (FW) modeling from clinically acquired diffusion MRI (DTI-like acquisitions) can be sensitive to this phenomenon. This FW index measures the fraction of the diffusion signal explained by isotropically unconstrained water, as estimated from a bi-tensor model. In this study, we developed a simple but powerful whole-brain FW measure des… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
79
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 52 publications
15
79
2
2
Order By: Relevance
“…Lower FA T was also shown to be associated with lower memory score in the body of the fornix. 58 In a study by Dumont et al, 34 patients with MCI and AlzD exhibited elevated FW in corticospinal tracts and bundles of the limbic system (such as the cingulum and the fornix) compared with healthy controls; in addition, patients with AlzD showed broader pathology as compared with patients with MCI. Higher FW was maintained even after removing GM and CSF partial volume contamination using a WM mask.…”
Section: Applications Of Diffusion Mri In Neurodegenerative Diseasesmentioning
confidence: 98%
See 2 more Smart Citations
“…Lower FA T was also shown to be associated with lower memory score in the body of the fornix. 58 In a study by Dumont et al, 34 patients with MCI and AlzD exhibited elevated FW in corticospinal tracts and bundles of the limbic system (such as the cingulum and the fornix) compared with healthy controls; in addition, patients with AlzD showed broader pathology as compared with patients with MCI. Higher FW was maintained even after removing GM and CSF partial volume contamination using a WM mask.…”
Section: Applications Of Diffusion Mri In Neurodegenerative Diseasesmentioning
confidence: 98%
“…Thus, in these voxels the metrics of bi-tensor DTI are liable to misestimation, since some signals arising from the fiber bundles not fitted to the single fiber tensor will be considered FW. 34 Finally, the bi-tensor model does not account for the non-Gaussian part of the diffusion decay. 8 Neurite Orientation Dispersion and Density Imaging NODDI is a multishell diffusion technique that enables more specific characterization of the tissue microstructure in the whole brain using a clinically feasible protocol.…”
Section: Diffusion Mri Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Dumont et al. showed that the free water compartment differentiates MCI from AD [69] . Our results corroborate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies analyzing the effects of including a FWM focus on scalar-valued maps such as fractional anisotropy (FA) derived from dMRI measurements. Measurable effects were shown for associations with delusions in chronic schizophrenia [6], stress-related neural pathology in depression [7], classification of Parkinson's disease and atypical parkinsonism [8], target definition in glioblastoma radiotherapy [9], as well as for the diagnosis of mild cognitive impairment and Alzheimer's disease [10].…”
Section: Introductionmentioning
confidence: 99%